The Contractor State and Its Implications, 1659-1815 - Solbes Ferri, Sergio (Servicio de Publicaciones y Difusión Científica de la ULPGC, 2012)
Sinopsis Este libro pretende acercar el gasto público al debate sobre la construcción de los estados modernos. La obtención de fondos para apoyar el Ejército y la Armada fue el principal deseo del estado mercantilista preindustrial. Solo el estado contratista es lo suficientemente fuerte para cubrir la demanda militar de hombres, equipos, armas y alimentos; lo que supone una gran oportunidad para los sectores económicos que se movilizaron para satisfacer la demanda pública y conseguir sus propios objetivos. Abstract This book aims to bring public spending to the debate on the construction of modern States. Funding to support the army and Navy was the main desire of the pre-industrial mercantilist State. Only the contractor State is strong enough to meet the demand for military men, equipment, weapons and food; which leads to a great opportunity for economic sectors that were mobilized to meet the public demand and achieve their own goals.